Apical leaf necrosis as a defence mechanism against pathogen attack: effects of high nutrient availability on onset and rate of necrosis - van den Berg, F; van den Bosch, F; Powers, S.J; Shaw, M.W (Plant pathology, 2008)
An outdoor experiment was conducted to increase understanding of apical leaf necrosis in the presence of pathogen infection. Holcus lanatus seeds and Puccinia coronata spores were collected from two adjacent and otherwise similar habitats with differing long-term N fertilization levels. After inoculation, disease and necrosis dynamics were observed during the plant growing seasons of 2003 and 2006. In both years high nutrient availability resulted in earlier disease onset, a higher pathogen population growth rate, earlier physiological apical leaf necrosis onset and a reduced time between disease onset and apical leaf necrosis onset. Necrosis rate was shown to be independent of nutrient availability. The results showed that in these nutrient-rich habitats H. lanatus plants adopted necrosis mechanisms which wasted more nutrients. There was some indication that these necrosis mechanisms were subject to local selection pressures, but these results were not conclusive. The findings of this study are consistent with apical leaf necrosis being an evolved defence mechanism.